Pengaruh Profitabilitas Dan Likuiditas Terhadap Nilai Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia: The Effect of Profitability and Liquidity on the Value of Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange - Maria Susanti Riong; Denny Erica; Dewi Retno Budiastuti (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstracts - effect of profitability and liquidity on firm value in the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2024. Profitability is measured using Return on Assets (ROA), while liquidity is measured using the Current Ratio. Firm value is assessed using the Price to Book Value (PBV) ratio. This research employs a quantitative approach with purposive sampling on 36 companies that meet the criteria. The data were analyzed using classical assumption tests, multiple linear regression, t-test (partial), and F-test (simultaneous), processed with SPSS version 25. The results show that partially, profitability has a positive but not significant effect on firm value, while liquidity has a negative and significant effect on firm value. Simultaneously, profitability and liquidity have a non-significant effect on firm value. These findings indicate that although both independent variables contribute to explaining variations in firm value, their influence is not strong enough to significantly shape positive investor perceptions. Therefore, companies need to strategically and comprehensively manage their financial performance to enhance their firm value in the eyes of investors.